Striatal-cortical dysconnectivity underlies somatosensory deficits in Parkinson's disease: Insights from rhythmic auditory-motor training - Cheng-Wei Huang; Hsin-Yun Tsai; Yi-Hsuan Lin; Wen-Wei Lin; Chin-Hsien Lin; Ming-Tsung Tseng (Neurobiology of Disease)
Evidence indicates that neurodegenerative diseases spread through distinct brain networks. For Parkinson's disease (PD), somatosensory abnormalities may accompany motor dysfunction in early disease stages when dopaminergic degeneration is limited to the basal ganglia. It remains unclear whether, based on the network-spread account, these abnormalities emanated from aberrant functional connectivity with the basal ganglia, and whether interventions normalizing this connectivity could reverse these abnormalities. Here, we employed functional MRI to record brain responses to tactile stimuli in patients with idiopathic PD and healthy controls before and after three-week rhythmic auditory stimulation-assisted gait (RASg) training. Consistent with the presence of striatal degeneration, patients showed right posterior putamen (pPut) hypoactivation when detecting tactile stimuli of their left leg. They also exhibited reduced functional connectivity from the right pPut to the right parietal somatosensory region (inferior parietal lobule, IPL), whose hypoactivation reflected patients' impaired tactile detectability. Importantly, this dysconnectivity predicted right IPL hypoactivation, indicating that pPut-IPL dysconnectivity underlay patients' impaired tactile detectability. Intriguingly, RASg training normalized patients' tactile detectability, which was mirrored by normalization of right IPL activation and pPut-IPL connectivity. Training-induced changes in pPut-IPL connectivity predicted changes in IPL activation during tactile detection, reinforcing the role of pPut-IPL connectivity in patients' tactile detectability. These findings suggest that somatosensory abnormalities in PD may arise from the spread of striatal pathology to relevant cortical regions. Rhythmic auditory-motor training acts to recover striatal connectivity, improving PD patients' somatosensory deficits.